Evaluation of root debridement skill in periodontology module/ Erni Noor ... [et al.] - Noor, Erni; Al-Bayaty, Fouad Hussain; Mohd Shukri, Muhammad Qadri; Zulkiflee, Mohamad Syahir (2019)
Objective: To evaluate the root debridement skill in periodontology pre-clinical module among dental students and to estimate the effectiveness of conducting periodontology pre-clinical module before entering clinical module. Materials and Method: A total of 47 pre-clinical dental students (Year 2) were included in this study. Single rooted extracted teeth were collected, mounted on acrylic resin and set into the level of 1/3 of the root length. Each of them were instructed to prepare a mounted teeth and to perform root debridement procedure on the labial surface of the tooth only within 10 minutes using Gracey curette #5/6. The similar samples were distributed back to the same students (which were already in clinical year (year 4) to repeat the same procedure on the lingual surface of the same tooth. Root surface roughness was evaluated by using scanning electron microscope (SEM) and profilometer for both labial and lingual surfaces. Statistical analysis was done using Mann-Whitney U test and T-test. Significance level of p ≤ 0.05 was assumed for all analysis. Results: SEM photomicrographs of root surfaces with magnifications of 100x and 800x revealed that there were incomplete removal of the dental calculus in both surfaces and significant roughness root surfaces noted. Conclusion: No significant differences noted between the students' root debridement skill in the pre-clinical and also clinical year. Objectives of the current module were fulfilled but in order to meet the highest standard, current module need to be improved in the future.